Insight into rock thermal conductivities in the North Croatian Basin through in situ measurements (Rudarsko-geološko-naftni zbornik, 2024)
The thermal conductivity of rocks represents one of the significant variables when investigating geothermal potential of an area on a local scale as well as regionally when performing basin analysis with the aim of estimating hydrocarbon potential. While steady-state methods of measuring thermal conductivity are presumed to yield more reliable results, transient methods allow for in situ measurements, thereby considerably simplifying and reducing measurement costs. This study was performed with the goal to expand the understanding of thermal conductivity of rocks typical for the North Croatian Basin (NCB) infill, as well as the underlying basement rocks. The measured values reveal distinct ranges across various lithologies. The thermal conductivity values measured in crystalline rocks are quite consistent, showing narrow ranges of values for each lithotype: for granite the measured values are between 2.317 and 2.486 W m-1 K-1, the value range for gneiss is between 3.332 and 3.565 W m-1 K-1 and the thermal conductivity of amphibolite is in the range between 1.549 and 1.623 W m-1 K-1. In contrast, the thermal conductivity values of sedimentary rocks vary within broader ranges – the values in sandstones range between 1.778 and 2.433 W m-1 K-1, for marlstones the registered range is between 0.917 and 2.323 W m-1 K-1, the values measured in shales range between 0.894 and 2.304 W m-1 K-1 and biocalcarenites show values of thermal conductivity between 0.990 and 2.023 W m-1 K-1. The greater variability in values measured for sedimentary rocks is attributed to the variability in porosity and fluid saturation, as well as the greater variability of mineral composition. Further research is needed to determine which factor has the greatest influence on the variability of thermal conductivity values, i.e. to establish to which extent each of the factors contributes to the measured values.